Polymer composite solid electrolyte membrane and preparation method thereof
By adding HNTs and additives to the polymer composite solid electrolyte membrane and using ultrasonic treatment and hot pressing technology, the problems of low conductivity, poor mechanical strength and insufficient interface stability are solved, and high ionic conductivity and good mechanical properties are achieved.
Patent Information
- Application Number
- CN202411472512.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-10-22
AI Technical Summary
The polymer composite solid electrolyte membrane has a low ionic conductivity and insufficient mechanical strength and interface stability after film formation, which limits its application in electric vehicles and other fields.
By adding functional agents HNTs and additives to the polymer substrate, using room temperature sonication and hot pressing technology, a solid electrolyte membrane with high ionic conductivity was prepared.
The room temperature ionic conductivity of polymer solid electrolyte is improved, mechanical strength and interface stability are enhanced, and electrochemical performance is improved.
Smart Images

Figure CN119650831A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid-state batteries, and in particular to a process for preparing a polymer composite solid-state electrolyte membrane. Background Art
[0002] With the development of the electric vehicle industry, lithium-ion batteries have become the core of new energy technology. As the technology evolves, the limitations of traditional liquid lithium-ion batteries are gradually becoming apparent. Solid-state batteries, with their innovative electrolyte design and material advantages, have demonstrated the ability to surpass lithium batteries in terms of safety and energy density.
[0003] Solid electrolytes are the core materials of all-solid-state batteries. As a type of solid electrolyte, polymer electrolytes have the characteristics of high ionic conductivity, good processing performance and low cost, making them the most widely used electrolytes in solid-state batteries. In polymer composite solid electrolyte membranes, the movement of polymer segments and the ionic conduction of inorganic solid electrolytes work together to achieve the transmission of lithium ions. The movement of polymer segments can provide a migration channel for lithium ions, while the inorganic solid electrolyte provides a region of high ionic conductivity, allowing lithium ions to be quickly transported within the membrane. Ionic conductivity needs to be improved: Although the ionic conductivity of polymer composite solid electrolyte membranes has improved to a certain extent compared with pure polymer electrolytes, there is still a certain gap compared with liquid electrolytes. Under low temperature conditions, the ionic conductivity will be further reduced, affecting the performance of the battery. Interface stability issues: The interface stability between the electrolyte membrane and the electrode is still a challenge. During the long-term charging and discharging process, chemical reactions, element diffusion and other phenomena may occur at the interface, resulting in an increase in interface resistance, affecting the performance and life of the battery. High cost: At present, the preparation cost of polymer composite solid electrolyte membranes is high, mainly due to the high price of inorganic solid electrolyte materials and the complex preparation process. This limits its application in large-scale energy storage and electric vehicles. When the battery is charged, lithium ions migrate from the positive electrode to the negative electrode through the electrolyte membrane; when discharging, lithium ions return from the negative electrode to the positive electrode, thus completing the battery's charge and discharge process. However, common polymer solid electrolytes have low ionic conductivity at room temperature and a small electrochemical window. At the same time, pure polymer solid electrolytes have disadvantages such as poor mechanical strength and poor interface stability after film formation, which limits their application to a certain extent.
[0004] Therefore, how to improve the conductivity of polymer solid electrolytes and enhance the mechanical strength and interface stability after film formation is an issue that the industry urgently needs to solve. Summary of the invention
[0005] A main purpose of the present invention is to overcome at least one defect of the above-mentioned prior art and to provide a polymer composite solid electrolyte membrane and a preparation method thereof which can improve the conductivity of the polymer solid electrolyte and enhance the mechanical strength and interface stability after film formation.
[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0007] According to one aspect of the present invention, there is provided a method for preparing a polymer composite solid electrolyte membrane, comprising the following steps:
[0008] Step 1: dispersing the polymer substrate in an organic solvent at a mass ratio of 0.05-0.8, stirring until completely dissolved, to obtain a polymer solution; adding lithium salt to the polymer solution and stirring;
[0009] Step 2: The mass ratio of functional agent HNTs to organic solvent is 0.01-0.1, the HNTs particles are dispersed in the organic solvent, and ultrasonic treatment is performed at room temperature to obtain HNTs turbid solution;
[0010] Step 3: dispersing the additive particles in the organic solvent at a mass ratio of 0.01-0.1, and performing ultrasonic treatment at room temperature to obtain an additive turbid solution;
[0011] Step 4: Pour the HNTs and additive turbid solution into the solution obtained in step 1 respectively, and stir to obtain electrolyte slurry;
[0012] Step 5: pour the electrolyte slurry into a polytetrafluoroethylene mold and perform vacuum drying to obtain a polymer composite solid electrolyte layer. Aluminum foil is placed on both sides of the polymer solid electrolyte layer and placed in a hot press to obtain a final solid electrolyte membrane.
[0013] According to one embodiment of the present invention, the polymer substrate is at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polycarbonate, polyacrylonitrile, polymethyl methacrylate and polyimide.
[0014] According to one embodiment of the present invention, the organic solvent is at least one of ethanol, acetonitrile, N,N-dimethylformamide, tetrahydrofuran, succinonitrile, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0015] According to one embodiment of the present invention, the lithium salt in step 1 is at least one of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl imide), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate and lithium trifluoromethanesulfonate.
[0016] According to one embodiment of the present invention, the additive is at least one of a solid electrolyte material and a nano oxide material.
[0017] According to one embodiment of the present invention, the solid electrolyte material is lithium lanthanum zirconium oxide and / or lithium titanium aluminum phosphate, and the particle size of the solid electrolyte material is less than 300 nm.
[0018] According to one embodiment of the present invention, the nano oxide material includes one or a combination of two or more of nano SiO2, nano Al2O3, nano TiO2, nano ZrO2, and nano ZnO.
[0019] According to one embodiment of the present invention, the mass percentage of the polymer substrate, the functional agent HNTs, the additive and the lithium salt is (10-85): (5-20): (5-50): (5-50).
[0020] According to one embodiment of the present invention, in step five, the hot pressing temperature is 30-60° C., the pressure is 0.1T-1T, the hot pressing time is 10-30S, and the thickness of the polymer solid electrolyte after film formation is 10-100 μm.
[0021] In order to achieve the above-mentioned object of the invention, the present invention also adopts the following technical scheme:
[0022] According to another aspect of the present invention, a polymer composite solid electrolyte membrane is provided, which is formed by using the preparation method as described above.
[0023] It can be seen from the above technical solutions that the advantages and positive effects of the polymer composite solid electrolyte membrane and method of the present invention are:
[0024] In the present invention, the prepared solid electrolyte slurry is uniform and has no particle agglomeration. In terms of the composition of the composite solid electrolyte, the addition of the functional agent HNTs can utilize the abundant negative charges on the surface to bind Li+, play a role in transmitting lithium ions, and secondly enhance the mechanical strength of the solid electrolyte membrane. The addition of additives can increase the amorphousness of the polymer solid electrolyte and improve the ionic conductivity. The solid electrolyte formed by the combination of points, lines and surfaces among the three has high room temperature ionic conductivity, which helps to improve the electrochemical performance. The present invention improves the conductivity of the polymer solid electrolyte and improves the mechanical strength and interface stability after film formation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a cycle life curve diagram of the solid electrolyte membrane obtained in Example 1 of the present invention used in a solid-state battery. DETAILED DESCRIPTION
[0026] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present invention will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted.
[0027] In the following description of different examples of the present invention, reference is made to the accompanying drawings, which form a part of the present invention and in which different exemplary structures, systems and steps that can implement multiple aspects of the present invention are shown by way of example. It should be understood that other specific schemes of components, structures, exemplary devices, systems and steps can be used, and structural and functional modifications can be made without departing from the scope of the present invention. Moreover, although the terms "top", "bottom", "front", "rear", "side", etc. may be used in this specification to describe different exemplary features and elements of the present invention, these terms are used herein only for convenience, such as according to the direction of the examples described in the accompanying drawings. Nothing in this specification should be construed as requiring a specific three-dimensional orientation of the structure to fall within the scope of the present invention.
[0028] The present invention obtains a solid electrolyte membrane with high ionic conductivity by compounding HNTs, additives and polymers. The present invention obtains a composite solid electrolyte slurry with uniform mixing and no particle agglomeration in steps, and further prepares a solid electrolyte membrane with the characteristics of high ionic conductivity and high mechanical processing strength.
[0029] The present invention provides a method for preparing a polymer composite solid electrolyte membrane;
[0030] In order to implement the above-mentioned purpose of the present invention, the following technical scheme is adopted:
[0031] A method for preparing a polymer composite solid electrolyte membrane comprises the following steps:
[0032] Step 1: dispersing the polymer substrate in an organic solvent at a mass ratio of 0.05-0.8, stirring until completely dissolved, to obtain a polymer solution; adding lithium salt to the polymer solution and stirring;
[0033] Step 2: The mass ratio of functional agent HNTs to organic solvent is 0.01-0.1, the HNTs particles are dispersed in the organic solvent, and ultrasonic treatment is performed at room temperature to obtain HNTs turbid solution;
[0034] Step 3: dispersing the additive particles in the organic solvent at a mass ratio of 0.01-0.1, and performing ultrasonic treatment at room temperature to obtain an additive turbid solution;
[0035] Step 4: Pour the HNTs and additive turbid solution into the solution obtained in step 1 respectively, and stir to obtain electrolyte slurry;
[0036] Step 5: Pour the electrolyte slurry into a polytetrafluoroethylene mold and perform vacuum drying to obtain a polymer composite solid electrolyte layer. Place aluminum foil on both sides of the polymer solid electrolyte layer and heat press it in a hot press to obtain a final solid electrolyte membrane.
[0037] The polymer substrate includes at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polycarbonate, polyacrylonitrile, polymethyl methacrylate and polyimide.
[0038] The lithium salt in step 1 includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl imide), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate and lithium trifluoromethanesulfonate.
[0039] The organic solvent includes at least one of ethanol, acetonitrile, N,N-dimethylformamide, tetrahydrofuran, succinonitrile, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
[0040] The above-mentioned additives include at least one of solid electrolyte materials and nano oxide materials, wherein the solid electrolyte material is lithium lanthanum zirconium oxide (LLZO) and lithium aluminum titanium phosphate (LATP); preferably, the particle size of the solid electrolyte material is less than 300nm, and the nano oxide material includes nano SiO2, nano Al2O3, nano TiO2, nano ZrO2, and nano ZnO; preferably, the particle size of the solid electrolyte material is less than 50nm.
[0041] The mass percentages of the polymer substrate, the functional agent HNTs, the additive and the lithium salt are (10-85):(5-20):(3-50):(20-50).
[0042] In the step 5, the hot pressing temperature is 30-50° C., the pressure is 0.1T-1T, the hot pressing time is 10-30S, and the thickness of the polymer solid electrolyte after film formation is 10-100 μm.
[0043] The beneficial effects of the present invention are as follows: HNTs are tubular structures with relatively regular morphology, and the surface electronegativity is conducive to promoting the dissociation of lithium salts, providing stable lithium ion transmission channels, reducing the diffusion energy barrier of lithium ions, and increasing the migration number of lithium ions, thereby improving the ionic conductivity of polymer solid electrolytes; in addition, the additive also reduces the crystallinity of the polymer, thereby improving the ionic conductivity of the polymer solid electrolyte, thereby improving the lithium ion cycle performance. The polymer substrate, the functional agent HNTs, and the additive provide the transmission of lithium ions on the surface, line, and point respectively, and the three are combined to improve the ionic conductivity of the solid electrolyte.
[0044] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0045] Example 1
[0046] (1) dissolving 10 g of polyethylene oxide in 50 g of acetonitrile and stirring with a magnetic stirrer until the mixture is completely dissolved to obtain a polymer solution;
[0047] (2) adding 2 g of lithium trifluoromethanesulfonate to the polymer solution of step (1) and stirring until completely dissolved;
[0048] (3) adding 2 g of functional agent HNTs into 20 g of acetonitrile and subjecting to ultrasonic treatment at room temperature for 2 h to uniformly disperse the HNTs in the solvent to obtain a HNTs turbid solution;
[0049] (4) adding 1 g of LATP to 10 g of acetonitrile and subjecting to ultrasonic treatment at room temperature for 2 hours to uniformly disperse the LATP in the solvent to obtain an additive turbid solution;
[0050] (5) pouring the HNTs in step (3) and the LATP turbid solution in step (4) into the solution in step (2) respectively, and stirring to obtain an electrolyte slurry;
[0051] (6) Pour the electrolyte slurry described in step (5) into a polytetrafluoroethylene mold and perform vacuum drying at a vacuum degree of -0.3 MPa and a temperature of 60° C. for 12 hours to obtain a polymer composite solid electrolyte layer.
[0052] (7) Aluminum foil is placed on both sides of the polymer solid electrolyte layer in step (6), and the layer is placed in a hot press and hot-pressed at 40° C., 0.2T, and 20S to obtain a final solid electrolyte membrane.
[0053] Example 2
[0054] (1) dissolving 10 g of polyvinylidene fluoride-hexafluoropropylene in 150 g of N-methylpyrrolidone, and stirring with a magnetic stirrer until the mixture is completely dissolved to obtain a polymer solution;
[0055] (2) adding 3 g of lithium trifluoromethanesulfonate to the polymer solution of step (1) and stirring with a magnetic stirrer until completely dissolved;
[0056] (3) adding 5 g of functional agent HNTs into 20 g of N-methylpyrrolidone, and subjecting to ultrasonic treatment at room temperature for 2 hours to uniformly disperse the HNTs in the solvent to obtain a HNTs turbid solution;
[0057] (4) adding 2 g of nano-TiO2 to 50 g of N-methylpyrrolidone, and subjecting the mixture to ultrasonic treatment at room temperature for 2 hours to uniformly disperse the nano-TiO2 in the solvent to obtain an additive turbid solution;
[0058] (5) pouring the HNTs turbid solution of step (3) and the additive turbid solution of step (4) into the solution of step (2) respectively, and stirring to obtain an electrolyte slurry;
[0059] (6) Pour the electrolyte slurry described in step (5) into a polytetrafluoroethylene mold and perform vacuum drying at a vacuum degree of -0.3 MPa and a temperature of 80° C. for 12 hours to obtain a polymer composite solid electrolyte layer.
[0060] (7) Aluminum foil is placed on both sides of the polymer solid electrolyte layer in step (6), and the layer is placed in a hot press and hot-pressed at 30° C., 0.5T, and 20S to obtain a final solid electrolyte membrane.
[0061] Example 3
[0062] (1) dissolving 10 g of polyvinylidene fluoride in 200 g of N-methylpyrrolidone and stirring with a magnetic stirrer until the mixture is completely dissolved to obtain a polymer solution;
[0063] (2) adding 2.5 g of lithium trifluoromethanesulfonate to the polymer solution of step (1) and stirring with a magnetic stirrer until completely dissolved;
[0064] (3) adding 4 g of functional agent HNTs into 20 g of acetonitrile and subjecting to ultrasonic treatment at room temperature for 2 h to uniformly disperse the HNTs in the solvent to obtain a HNTs turbid solution;
[0065] (4) dispersing 3 g of nano-SiO2 in 50 g of N-methylpyrrolidone, and subjecting the mixture to ultrasonic treatment at room temperature for 2 hours to uniformly disperse the nano-SiO2 in the solvent to obtain an additive turbid solution;
[0066] (5) pouring the HNTs turbid solution of step (3) and the nano-SiO2 turbid solution of step (4) into the solution of step (2) respectively, and stirring to obtain an electrolyte slurry;
[0067] (6) Pour the electrolyte slurry described in step (5) into a polytetrafluoroethylene mold and perform vacuum drying at a vacuum degree of -0.3 MPa and a temperature of 80° C. for 12 hours to obtain a polymer composite solid electrolyte layer.
[0068] (7) Aluminum foil is placed on both sides of the polymer solid electrolyte layer in step (6), and the layer is placed in a hot press and hot-pressed at 50° C., 0.8 T, and 10 s to obtain a final solid electrolyte membrane.
[0069] Example 4
[0070] (1) dissolving 10 g of polyethylene oxide in 100 g of acetonitrile and stirring with a magnetic stirrer until the mixture is completely dissolved to obtain a polymer solution;
[0071] (2) adding 5 g of lithium trifluoromethanesulfonate to the polymer solution of step (1) and stirring with a magnetic stirrer until completely dissolved;
[0072] (3) adding 4 g of functional agent HNTs to 50 g of acetonitrile and subjecting to ultrasonic treatment at room temperature for 2 hours to uniformly disperse the HNTs in the solvent to obtain a HNTs turbid solution;
[0073] (4) dispersing 3 g of nano ZrO2 in 50 g of acetonitrile, and subjecting the mixture to ultrasonic treatment at room temperature for 2 hours to uniformly disperse the nano ZrO2 in the solvent to obtain an additive turbid solution;
[0074] (5) pouring the HNTs turbid solution of step (3) and the additive turbid solution of step (4) into the solution of step (2), respectively, and stirring for 6 hours with a magnetic stirrer to obtain an electrolyte slurry;
[0075] (6) Pour the electrolyte slurry described in step (5) into a polytetrafluoroethylene mold and perform vacuum drying at a vacuum degree of -0.3 MPa and a temperature of 60° C. for 12 hours to obtain a polymer composite solid electrolyte layer.
[0076] (7) Aluminum foil is placed on both sides of the polymer solid electrolyte layer in step (6), and the layer is placed in a hot press and hot-pressed at 35° C., 1T, and 10S to obtain a final solid electrolyte membrane.
[0077] Example 5
[0078] (1) dissolving 10 g of polyethylene oxide in 80 g of acetonitrile and stirring with a magnetic stirrer until the mixture is completely dissolved to obtain a polymer solution;
[0079] (2) adding 3 g of lithium trifluoromethanesulfonate to the polymer solution of step (1) and stirring with a magnetic stirrer until completely dissolved;
[0080] (3) adding 3 g of functional agent HNTs into 10 g of ethanol and subjecting to ultrasonic treatment at room temperature for 2 h to uniformly disperse the HNTs in the solvent to obtain a HNTs turbid solution;
[0081] (4) adding 1 g of LLZO to 10 g of acetonitrile and subjecting to ultrasonic treatment at room temperature for 2 hours to uniformly disperse LLZO in the solvent to obtain an additive turbid solution;
[0082] (5) pouring the HNTs turbid solution of step (3) and the additive turbid solution of step (4) into the solution of step (2), respectively, and stirring for 6 hours with a magnetic stirrer to obtain an electrolyte slurry;
[0083] (6) Pour the electrolyte slurry described in step (5) into a polytetrafluoroethylene mold and perform vacuum drying at a vacuum degree of -0.3 MPa and a temperature of 60° C. for 12 hours to obtain a polymer composite solid electrolyte layer.
[0084] (7) Aluminum foil is placed on both sides of the polymer solid electrolyte layer in step (6), and the layer is placed in a hot press and hot-pressed at 60° C., 0.8 T, and 20 s to obtain a final solid electrolyte membrane.
[0085] Example 6
[0086] (1) dissolving 8 g of polyethylene oxide and 2 g of polyvinylidene fluoride in 100 g of N,N-dimethylformamide, and stirring with a magnetic stirrer until the mixture is completely dissolved to obtain a polymer solution;
[0087] (2) adding 5 g of lithium bis(fluorosulfonyl)imide to the polymer solution of step (1) and stirring with a magnetic stirrer until completely dissolved;
[0088] (3) adding 5 g of functional agent HNTs to 20 g of N,N-dimethylformamide, and subjecting to ultrasonic treatment at room temperature for 2 hours to uniformly disperse the HNTs in the solvent to obtain a HNTs turbid solution;
[0089] (4) adding 1 g of LATP to 10 g of N,N-dimethylformamide, and subjecting the mixture to ultrasonic treatment at room temperature for 2 hours to uniformly disperse LLZO in the solvent to obtain an additive turbid solution;
[0090] (5) pouring the HNTs turbid solution of step (3) and the additive turbid solution of step (4) into the solution of step (2), respectively, and stirring for 6 hours with a magnetic stirrer to obtain an electrolyte slurry;
[0091] (6) Pour the electrolyte slurry described in step (5) into a polytetrafluoroethylene mold and perform vacuum drying at a vacuum degree of -0.3 MPa and a temperature of 80° C. for 12 hours to obtain a polymer composite solid electrolyte layer.
[0092] (7) Aluminum foil is placed on both sides of the polymer solid electrolyte layer described in step (6), and the layer is placed in a hot press and hot-pressed at 50° C., 0.3T, and 30S to obtain a final solid electrolyte membrane.
[0093] Example 7
[0094] (1) dissolving 8 g of polyethylene oxide and 2 g of polyvinylidene fluoride in 100 g of N,N-dimethylformamide, and stirring with a magnetic stirrer until the mixture is completely dissolved to obtain a polymer solution;
[0095] (2) adding 3 g of lithium tetrafluoroborate to the polymer solution of step (1) and stirring with a magnetic stirrer until completely dissolved;
[0096] (3) adding 4 g of functional agent HNTs into 20 g of N,N-dimethylformamide, and subjecting to ultrasonic treatment at room temperature for 2 h to uniformly disperse the HNTs in the solvent to obtain a HNTs turbid solution;
[0097] (4) adding 2 g of nano ZrO2 to 10 g of acetonitrile and subjecting to ultrasonic treatment at room temperature for 2 hours to uniformly disperse the nano ZrO2 in the solvent to obtain an additive turbid solution;
[0098] (5) pouring the HNTs turbid solution of step (3) and the additive turbid solution of step (4) into the solution of step (2), respectively, and stirring for 6 hours with a magnetic stirrer to obtain an electrolyte slurry;
[0099] (6) Pour the electrolyte slurry described in step (5) into a polytetrafluoroethylene mold and perform vacuum drying at a vacuum degree of -0.3 MPa and a temperature of 80° C. for 12 hours to obtain a polymer composite solid electrolyte layer.
[0100] (7) Aluminum foil is placed on both sides of the polymer solid electrolyte layer in step (6), and the layer is placed in a hot press and hot-pressed at 40° C., 0.5T, and 30S to obtain a final solid electrolyte membrane.
[0101] Example 8
[0102] (1) dissolving 10 g of polyvinylidene fluoride-hexafluoropropylene in 50 g of N,N-dimethylformamide, and stirring with a magnetic stirrer until the mixture is completely dissolved to obtain a polymer solution;
[0103] (2) adding 4 g of lithium difluorooxalatoborate to the polymer solution of step (1) and stirring with a magnetic stirrer until completely dissolved;
[0104] (3) adding 3 g of functional agent HNTs into 20 g of N,N-dimethylformamide, and subjecting to ultrasonic treatment at room temperature for 2 h to uniformly disperse the HNTs in the solvent to obtain a HNTs turbid solution;
[0105] (4) adding 1 g of LATP to 10 g of acetonitrile and subjecting to ultrasonic treatment at room temperature for 2 hours to uniformly disperse LLZO in the solvent to obtain an additive turbid solution;
[0106] (5) pouring the HNTs turbid solution of step (3) and the additive turbid solution of step (4) into the solution of step (2), respectively, and stirring for 6 hours with a magnetic stirrer to obtain an electrolyte slurry;
[0107] (6) Pour the electrolyte slurry described in step (5) into a polytetrafluoroethylene mold and perform vacuum drying at a vacuum degree of -0.3 MPa and a temperature of 80° C. for 12 hours to obtain a polymer composite solid electrolyte layer.
[0108] (7) Aluminum foil is placed on both sides of the polymer solid electrolyte layer in step (6), and the layer is placed in a hot press and hot-pressed at 50° C., 0.2T, and 30S to obtain a final solid electrolyte membrane.
[0109] Example 9
[0110] (1) dissolving 2 g of polyethylene oxide and 8 g of polyvinylidene fluoride in 100 g of N,N-dimethylformamide, and stirring with a magnetic stirrer until the mixture is completely dissolved to obtain a polymer solution;
[0111] (2) adding 3 g of lithium bis(fluorosulfonyl)imide to the polymer solution of step (1) and stirring with a magnetic stirrer until completely dissolved;
[0112] (3) adding 4 g of functional agent HNTs into 20 g of N,N-dimethylformamide, and subjecting to ultrasonic treatment at room temperature for 2 h to uniformly disperse the HNTs in the solvent to obtain a HNTs turbid solution;
[0113] (4) adding 1 g of nano ZrO2 to 10 g of N,N-dimethylformamide, and subjecting the mixture to ultrasonic treatment at room temperature for 2 hours to disperse the nano ZrO2 in the solvent to obtain an additive turbid solution;
[0114] (5) pouring the HNTs turbid solution of step (3) and the additive turbid solution of step (4) into the solution of step (2), respectively, and stirring for 6 hours with a magnetic stirrer to obtain an electrolyte slurry;
[0115] (6) Pour the electrolyte slurry described in step (5) into a polytetrafluoroethylene mold and perform vacuum drying at a vacuum degree of -0.3 MPa and a temperature of 80° C. for 12 hours to obtain a polymer composite solid electrolyte layer.
[0116] (7) Aluminum foil is placed on both sides of the polymer solid electrolyte layer in step (6), and the layer is placed in a hot press and hot-pressed at 40° C., 0.2T, and 30S to obtain a final solid electrolyte membrane.
[0117] Example 10
[0118] (1) dissolving 10 g of polymethyl methacrylate in 60 g of acetonitrile and stirring with a magnetic stirrer until the mixture is completely dissolved to obtain a polymer solution;
[0119] (2) adding 3 g of lithium difluorooxalatoborate to the polymer solution of step (1) and stirring with a magnetic stirrer until completely dissolved;
[0120] (3) adding 2 g of functional agent HNTs into 20 g of acetonitrile and subjecting to ultrasonic treatment at room temperature for 2 h to uniformly disperse the HNTs in the solvent to obtain a HNTs turbid solution;
[0121] (4) adding 1 g of LATP and 1 g of nano-Al2O3 into 50 g of acetonitrile, and subjecting to ultrasonic treatment at room temperature for 2 hours to uniformly disperse LATP and nano-Al2O3 in the solvent to obtain an additive turbid solution;
[0122] (5) pouring the HNTs turbid solution of step (3) and the additive turbid solution of step (4) into the solution of step (2), respectively, and stirring for 6 hours with a magnetic stirrer to obtain an electrolyte slurry;
[0123] (6) Pour the electrolyte slurry described in step (5) into a polytetrafluoroethylene mold and perform vacuum drying at a vacuum degree of -0.3 MPa and a temperature of 60° C. for 12 hours to obtain a polymer composite solid electrolyte layer.
[0124] (7) Aluminum foil is placed on both sides of the polymer solid electrolyte layer described in step (6), and the layer is placed in a hot press and hot-pressed at 50° C., 0.5T, and 20S to obtain a final solid electrolyte membrane.
[0125] The following are two examples of existing preparation methods for forming solid electrolyte membranes.
[0126] Comparative Example 1
[0127] (1) dissolving 8 g of polyethylene oxide in 60 g of acetonitrile and stirring with a magnetic stirrer until the mixture is completely dissolved to obtain a polymer solution;
[0128] (2) adding 1 g of lithium trifluoromethanesulfonate to the polymer solution of step (1) and stirring with a magnetic stirrer until completely dissolved;
[0129] (3) Pour the slurry described in step (2) into a polytetrafluoroethylene mold and perform vacuum drying at a vacuum degree of -0.3 MPa and a temperature of 60° C. for 12 hours to obtain a polymer composite solid electrolyte layer.
[0130] (4) Aluminum foil is placed on both sides of the polymer solid electrolyte layer in step (3), and the layer is placed in a hot press and hot-pressed at 30° C., 0.1 T, and 30 s to obtain a final solid electrolyte membrane.
[0131] Comparative Example 2
[0132] (1) dissolving 10 g of polyvinyl carbonate in 80 g of ethanol and stirring with a magnetic stirrer until the mixture is completely dissolved to obtain a polymer solution;
[0133] (2) adding 2 g of lithium trifluoromethanesulfonate to the polymer solution of step (1) and stirring with a magnetic stirrer until completely dissolved;
[0134] (3) adding 3 g of nano ZrO2 to 15 g of acetonitrile and subjecting to ultrasonic treatment at room temperature for 2 hours to disperse the nano ZrO2 in the solvent to obtain an additive turbid solution;
[0135] (4) pouring the additive turbid solution of step (3) into the solution of step (2) respectively, and stirring for 6 hours by a magnetic stirrer to obtain an electrolyte slurry;
[0136] (5) Pour the electrolyte slurry described in step (4) into a polytetrafluoroethylene mold and perform vacuum drying at a vacuum degree of -0.3 MPa and a temperature of 80° C. for 12 hours to obtain a polymer composite solid electrolyte layer.
[0137] (6) Aluminum foil is placed on both sides of the polymer solid electrolyte layer in step (5), and the layer is placed in a hot press and hot-pressed at 50° C., 0.8 T, and 30 s to obtain a final solid electrolyte membrane.
[0138] The electrolyte sheets obtained above were used for battery assembly and testing:
[0139] The composite polymer solid electrolyte sheet prepared above was combined with two stainless steel electrodes (SS) to form a SS / CSEs / SS simulated battery for testing. The battery assembly process was carried out in a glove box where the water and oxygen content was less than 0.1ppm. The electrochemical impedance of the composite polymer solid electrolyte was measured at room temperature using an alternating current impedance spectroscopy (EIS) test at a frequency range of 1Hz to 1MHz. The ionic conductivity of the prepared composite polymer solid electrolyte was calculated using the impedance data obtained from the EIS test.
[0140] The composite polymer solid electrolyte membrane prepared above is combined with lithium iron phosphate (LiFePO4) positive electrode and lithium metal negative electrode to form a button cell. The preparation of the button cell is carried out in a glove box. The button cell is subjected to a charge and discharge cycle test at a rate of 0.1C, and the attenuation of its discharge capacity is detected.
[0141]
[0142]
[0143] Table 1
[0144] It can be seen from the data in Table 1 that compared with Comparative Examples 1 and 2, the electrolyte sheet obtained in Examples 1-10 has higher ionic conductivity at room temperature. It can be seen from the data in Table 1 that the button batteries assembled in Examples 1-10 have better cycle performance, while the button batteries assembled in Comparative Examples 1 and 2 have extremely poor cycle performance.
[0145] Figure 1 This is a cycle life curve diagram of the solid electrolyte membrane obtained in Example 1 of the present invention used in a solid-state battery. Figure 1 The cycle life curve of the solid electrolyte membrane obtained in Example 1 for solid-state batteries is shown. After more than 100 cycles, the gram capacity of LiFePO4 in Example 1 is still maintained at more than 140 mAh / g. It can be seen that the composite polymer solid electrolyte membrane of the present invention not only has a high ion conductivity at room temperature, but also applies the composite polymer solid electrolyte membrane to the battery to improve the cycle performance of the battery.
[0146] Finally, the polymer composite solid electrolyte membrane provided by the present invention. According to an embodiment of the present invention, the polymer solid electrolyte membrane comprises a polymer substrate, a functional agent, an additive and a lithium salt, wherein the functional agent is halloysite multi-walled nanotubes.
[0147] Halloysite multi-walled nanotubes (HNTs, Al2Si2O5(OH)4·nH2O) are natural, environmentally friendly, low-cost, biocompatible, thermally stable and mechanically stable natural clay materials. They have a nano hollow multi-walled tube structure and are formed by a multilayer structure of aluminum oxide octahedra and adjacent silicon tetrahedron layers. Their surface is negatively charged within a wide pH range. These active points make it possible for the widespread use of halloysite. HNTs have unique and excellent properties such as large aspect ratio, high strength, good corrosion resistance, good thermal conductivity and high electrical conductivity. The present invention uses HNTs as a functional agent for a polymer substrate to construct a light skeleton (three-dimensional porous coating), providing a fast ion transport channel and thus improving ion conductivity. At the same time, the construction of the inorganic framework also improves the mechanical strength of the polymer solid electrolyte layer.
[0148] Although the embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and cannot be understood as limiting the present invention. A person of ordinary skill in the art may change, modify, replace and modify the above embodiments within the scope of the present invention. A person of ordinary skill in the technical field to which the present invention belongs shall understand that the specific structures and process steps shown in the above specific implementation methods are merely exemplary and non-restrictive. Moreover, a person of ordinary skill in the technical field to which the present invention belongs may combine the various technical features shown above in various possible ways to form a new technical solution, or make other changes, all of which are within the scope of the present invention.
Claims
1. A method for preparing a polymer composite solid electrolyte membrane, characterized in that: The following steps are involved: Step 1: dispersing the polymer substrate in an organic solvent at a mass ratio of 0.05-0.8, stirring until completely dissolved, to obtain a polymer solution; adding lithium salt to the polymer solution and stirring; Step 2: The mass ratio of functional agent HNTs to organic solvent is 0.01-0.1, the HNTs particles are dispersed in the organic solvent, and ultrasonic treatment is performed at room temperature to obtain HNTs turbid solution; Step 3: dispersing the additive particles in the organic solvent at a mass ratio of 0.01-0.1, and performing ultrasonic treatment at room temperature to obtain an additive turbid solution; Step 4: Pour the HNTs and additive turbid solution into the solution obtained in step 1 respectively, and stir to obtain electrolyte slurry; Step 5: pour the electrolyte slurry into a polytetrafluoroethylene mold and perform vacuum drying to obtain a polymer composite solid electrolyte layer. Aluminum foil is placed on both sides of the polymer solid electrolyte layer and placed in a hot press to obtain a final solid electrolyte membrane.
2. The method for preparing a polymer composite solid electrolyte membrane according to claim 1, characterized in that: The polymer substrate is at least one of polyethylene oxide, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polycarbonate, polyacrylonitrile, polymethyl methacrylate and polyimide.
3. The method for preparing a polymer composite solid electrolyte membrane according to claim 1, characterized in that: The organic solvent is at least one of ethanol, acetonitrile, N,N-dimethylformamide, tetrahydrofuran, succinonitrile, N,N-dimethylacetamide, dimethyl sulfoxide and N-methylpyrrolidone.
4. The method for preparing a polymer composite solid electrolyte membrane according to claim 1, characterized in that: The lithium salt in step 1 is at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl imide), lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(fluorosulfonyl imide), lithium difluorooxalatoborate and lithium trifluoromethanesulfonate.
5. The method for preparing a polymer composite solid electrolyte membrane according to claim 1, characterized in that: The additive is at least one of a solid electrolyte material and a nano oxide material.
6. The method for preparing a polymer composite solid electrolyte membrane according to claim 5, characterized in that: The solid electrolyte material is lithium lanthanum zirconium oxide and / or lithium titanium aluminum phosphate, and the particle size of the solid electrolyte material is less than 300 nm.
7. The method for preparing a polymer composite solid electrolyte membrane according to claim 5, characterized in that: The nano oxide material includes one or a combination of two or more of nano SiO2, nano Al2O3, nano TiO2, nano ZrO2 and nano ZnO.
8. The method for preparing a polymer composite solid electrolyte membrane according to claim 1, characterized in that: The mass percentages of the polymer substrate, the functional agent HNTs, the additive and the lithium salt are (10-85):(5-20):(5-50):(5-50).
9. The method for preparing a polymer composite solid electrolyte membrane according to claim 1, characterized in that: In the step 5, the hot pressing temperature is 30-60° C., the pressure is 0.1T-1T, the hot pressing time is 10-30S, and the thickness of the polymer solid electrolyte after film formation is 10-100 μm.
10. A polymer composite solid electrolyte membrane, characterized in that: A polymer composite solid electrolyte membrane is formed using the preparation method as described in claims 1 to 9.
Citation Information
Patent Citations
Composite solid polymer electrolyte film and preparation method and application thereof
CN109546207A
Preparation method and application of high-strength solid electrolyte membrane
CN111106391A
Solid polymer electrolyte membrane and manufacturing method thereof
CN114006032A
Halloysite nanotube-polymer matrix hybrid solid electrolyte membrane and preparation method thereof
CN117577948A